2017
DOI: 10.1002/pts.2319
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Finger Motion Coordination during Packaging Interactions

Abstract: Packaging accessibility is a significant problem for many older people. Whilst the majority of studies have focused on issues surrounding strength, work has shown that dexterity required to open a pack is also a major issue for many older people. Hence, the work undertaken here reports a quantitative study that aimed to analyse motion coordination patterns across digits 2–5 (index to little finger) during interactions with three of the most common types of packaging: plastic bottles, jars and crisps packets, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
(51 reference statements)
1
4
0
Order By: Relevance
“…In order to collate and compare the data from the correlation maps, a graph was produced that compares the number of occasions where the correlation was below 0.5, weakly correlated, and above 0.85, strongly correlated. This corroborates the methodology used in a study by Yoxall et al, in which the same scales are employed.…”
Section: Data Processingsupporting
confidence: 89%
See 1 more Smart Citation
“…In order to collate and compare the data from the correlation maps, a graph was produced that compares the number of occasions where the correlation was below 0.5, weakly correlated, and above 0.85, strongly correlated. This corroborates the methodology used in a study by Yoxall et al, in which the same scales are employed.…”
Section: Data Processingsupporting
confidence: 89%
“…The PPT is a standard dexterity test used in hand therapy and rehabilitation, consisting of a series of pegs placed in holes (or washers and collars placed on pegs previously placed in holes) and the numbers of pegs placed in a measured amount of time is purported to relate to a participant's dexterity . Subsequent work by Yoxall et al showed that there was a significant correlation between a participant's finger movements and perceived dexterous demand of the task. So tasks that had finger movements, where the fingers moved in a similar pattern at the same time were considered less dexterously demanding than tasks where the fingers moved separately.…”
Section: Introductionmentioning
confidence: 99%
“…not having sufficient grip strength to twist off the lid. Less work has been undertaken to understand dexterity and issues to access packaging relating to fine manipulation, but recent studies have sought to redress this (Yoxall et al, 2019;Yoxall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, some works analysed hand motion in patients recovering from stroke and other motor related impairments, revealing that trajectory smoothness was lower and movements were more segmented than in healthy subjects [51], [153]. In the same line, some works analysed measures such as jerk or velocities while healthy subjects were performing ADLs using certain products, in order to correlate those parameters with the dexterity required to manipulate the product, as in [154]. In that work, velocities and jerk were calculated during packaging interactions and the performance of the dexterity test Purdue Pegboard Test, finding out that speed and jerk were not correlated with the perceived level of dexterity.…”
Section: Velocity-related Analysesmentioning
confidence: 99%
“…Nevertheless, the rest of kinematic synergies were found to be task dependent, and diameter and weight of cylindric objects was found to affect hand kinematics, suggesting that analysing kinematic data while performing different tasks and using different products would be worthily, Contributions to hand kinematics characterisation during product manipulation in ADLs 86 contributing to analyse hand kinematic requirements while performing certain fields of tasks or using products with specific characteristics. Apart from PCA, methods such as correlation between joint angles have been used in literature in order to study finger motion coordination during product manipulation tasks such as packaging interactions [154]. In fact, this work compared (among other kinematic parameters) correlations between finger joints during packaging interactions and during the performance of the Purdue Pegboard Test, finding out that perceived required dexterity to perform the tasks was highly dependent of correlation between finger joints, perceiving less requirement of dexterity when fingers correlation was higher.…”
Section: Kinematic Synergies Analysesmentioning
confidence: 99%